Influence of a stressing constraint on stiffness and damping functions of a ski simulator's platform motion - Deschamps, T.; Nourrit, D.; Caillou, N.; Delignieres, D. (Journal of Sports Sciences, 2004)
The aim of this study was to assess the effect of stress on a previously acquired motor coordination. Following a longitudinal learning experiment, four participants performed oscillations on a ski simulator, either in normal or stressful conditions. The results showed that the amplitude of the oscillations decreased under stress, but no significant effect was seen regarding coordination, suggesting the strong resistance to stress of overlearned behaviour. Nevertheless, for one participant, a transient regression towards a former stage of learning was observed. This result was consistent with the regression hypothesis formulated by Fuchs (1962).